Development of digital filtering techniques in three-dimensional TLM models - Vongurai, Rawin (2013)
Digital filtering (DF) techniques are receiving significant interest, because they can represent fine features such as vias, thin-panels and thin-wires in full-field solutions of electromagnetic problems with significant savings in computational costs. However, a limitation of this technique is that DF can only represent a fine feature as a plane or as an internal boundary. In other words, an internal boundary can represent the electromagnetic properties of a fine feature in one dimension or two directions.